Pinus Susceptibility to Pitch Canker Triggers Specific Physiological Responses in Symptomatic Plants: An Integrated Approach - Amaral, Joana; Correia, Barbara; António, Carla; Rodrigues, Ana Margarida; Gómez-Cadenas, Aurelio; Valledor, Luis; Hancock, Robert D.; Alves, Artur; Pinto, Glória (Frontiers in Plant Science, 2019)
Fusarium circinatum, the causal agent of pine pitch canker (PPC), is an emergent and still understudied risk that threatens Pinus forests worldwide, with potential production and sustainability losses. In order to explore the response of pine species with distinct levels of susceptibility to PPC, we investigated changes in physiology, hormones, specific gene transcripts and primary metabolism occurring in symptomatic Pinus pinea, Pinus pinaster and Pinus radiata upon inoculation with F. circinatum. Pinus radiata and P. pinaster exhibiting high and intermediate susceptibility to PPC, respectively suffered changes in plant water status and photosynthetic impairment. This was associated with sink metabolism induction, a general accumulation of amino acids and overexpression of pathogenesis-related genes. On the other hand, P. pinea exhibited the greatest resistance to PPC and Stomatal opening, transpiration increase, and glycerol accumulation were observed in inoculated plants. A stronger induction of pyruvate decarboxylase transcripts and differential hormones regulation were also found for inoculated P. pinea in comparison with the susceptible Pinus species studied. The specific physiological changes reported herein are the first steps to understand the complex Pinus-Fusarium interaction and create tools for the selection of resistant genotypes thus contributing to disease mitigation.